Proteção das nascentes: o projeto “água e qualidade de vida” no município de Francisco Beltrão – PR - Capellari , Adalberto (2018)
Currently, despite efforts to contain waste and uncontrolled water consumption, it is becoming scarce and its quality deteriorating rapidly. It should be taken into account that water is one of the most important thing in the world, which deserves effective protection, especially water springs, in order to balance the availability of this resource with its demand. Aware of this problem, Petrobrás, through the Programa Petrobrás Ambiental, supported environmental preservation projects. ACESI - Associação do Centro de Educação Sindical, headquartered in Francisco Beltrão - PR, presented the project entitled "Water and Quality of Life", which aimed to preserve water springs, located in the counties of the southwestern region of Paraná. In this context, the present research had as objective to verify how the process of protection and preservation of the water springs, located in the rural properties in Francisco Beltrão-PR, are contemplated by the Project. It is an interdisciplinary research, characterized as qualitative-quantitative, exploratory and descriptive; as to the technique, it was used bibliographic studies and case study. The results showed that, about legal, economic and social perspective, water, and consequently the springs, need effective protection, because the possibility of its scarcity; in this sense, the project reached the objectives satisfactorily, since most of the water springs protected by the project, located in the rural properties of Francisco Beltrão - PR, are preserved. However, it is understood that there is still a lot os things to be done, constant public policies aimed at environmental education are needed, especially directed at raising awareness of the importance of the protection of springs, in order to be able to have water in quantity and quality, in the present and in the future.